Transcontinental Dissemination of the L2b/D-Da Recombinant Chlamydia trachomatis Lymphogranuloma venereum (LGV) Strain: Need of Broad Multi-Country Molecular Surveillance. (29th January 2021) - Borges, Vítor; Isidro, Joana; Correia, Cristina; Cordeiro, Dora; Vieira, Luís; Lodhia, Zohra; Fernandes, Cândida; Rodrigues, Ana Maria; Azevedo, Jacinta; Alves, João; Roxo, João; Rocha, Miguel; et al.
Abstract: Previously, we identified a Chlamydia trachomatis lymphogranuloma venereum (LGV) recombinant strain possessing a non-LGV ompA genotype. Here, culture-independent genome sequencing confirms its circulation in Europe, Middle East, and North America, and unveils emergence of antibiotic resistance. Broad surveillance is needed.